Energy Safety and Innovative Development of the BRICS States - Rodionova, Irina Aleksandrovna; Chernyaev, Maksim Vasilyevich; Korenevskaya, Anna Vadimovna (International Journal of Energy Economics and Policy, 2017)
In today’s world, transition from a model based on the use of world resources by a limited number of developed economies (primarily the USA, Western Europe, etc.), and on the redelivery of those to other regions and countries in the form of finished products and investments, to a multipolarity model is observed. Emerging new leaders, both regional and global, indicate formation of new centers of development. In this paper, the roles of BRICS member countries in the global economy are considered in context of multipolar world development process. For the further development of global economy, additional energy production is of great essence. However, power consumption efficiency and energy safety strategies move to the forefront in today’s world. BRICS play an important role in the Global Energy Safety system, and their energy industry has a significant weight in both generation and consumption of world’s power resources. The purpose of the article is to distinguish the BRICS position within the global power industry in dynamics from energy safety point of view, as cooperation in this field has great influence on the development and allows improving position of BRICS member countries in generating and export of industrial products and in general within the global economy. BRICS, the EU and NAFTA comparative analysis has been carried out based on the data provided by British oil and gas company British Petroleum (BP Statistical Review of World Energy 2016), the United Nations Industrial Development Organization and the US National Science Foundation (Science and Engineering Indicators 2016) over the period of 1999-2015. Keywords: BRICS, NAFTA, the EU, power industry, international ratings, R&D, innovative economy. JEL Classifications: O10, O31